Design and Implementation of a Car’s Black Box System Using a Raspberry Pi and a 4G Module - Abel Garcia-Barrientos; David Torres-Uresti; Francisco R. Castillo-Soria; Ulises Pineda-Rico; Jose Antonio Hoyo-Montaño; Obed Perez-Cortes; Patricio Ordaz-Oliver (Applied Sciences, 2022)
The design and implementation of a car’s black box system using a Raspberry Pi microcomputer and an Internet of things module is presented in this research. This system was built using a Raspberry Pi microcomputer and different sensors, including a GPS, camera module, audio module, alcohol sensor module, and signals from the electronic control unit. The data were stored in both a secure digital card and in the cloud using the Waveshare SIM7600G-H 4G module. The results show that this embedded system can acquire and process video, audio, GPS data, alcohol concentration, speed, temperature, etc. Finally, a graphics user interface was developed to process the stored files. This system is similar to a black box in airplanes, which records all flight information into the black box using a specific algorithm. This makes the recorded flight data accessible to authorities when needed.